Advances in CAR-NK cell therapy for hematological malignancies - Yang, Rui; Yang, Yun; Liu, Rui; Wang, Yiwen; Yang, Ruoyu; He, Aili (Frontiers in Immunology, 2024)
Chimeric antigen receptor T (CAR-T) cell therapy has revolutionized the treatment of hematological malignancies, demonstrably improving patient outcomes and prognosis. However, its application has introduced new challenges, such as safety concerns, off-target toxicities, and significant costs. Natural killer (NK) cells are crucial components of the innate immune system, capable of eliminating tumor cells without prior exposure to specific antigens or pre-activation. This inherent advantage complements the limitations of T cells, making CAR-NK cell therapy a promising avenue for hematological tumor immunotherapy. In recent years, preclinical and clinical studies have yielded preliminary evidence supporting the safety and efficacy of CAR-NK cell therapy in hematological malignancies, paving the way for future advancements in immunotherapy. This review aims to succinctly discuss the characteristics, significant therapeutic progress, and potential challenges associated with CAR-NK cell therapy.